Star wars. Attack of the clones [videorecording (Blu-Ray)] - Lucas, George, 1944-; Jackson, Samuel L.; McGregor, Ewan, 1971-; Portman, Natalie, 1981- (LucasFilm, 2019)
Ten years after the Trade Federation's hostilities against Naboo, Queen Amidala has traded in her crown for a seat on the Galactic Senate. An assassination attempt on Padme brings Anakin Skywalker and Obi-Wan Kenobi back into her life.